Dubliners: the journey westward - Magda Velloso Fernandes de Tolentino (1989)
This work aims at a study of James Joyce's VubZ-ín&Aò as a collection of stories with a unity of theme, scene and characters. The stories are seen here in their depiction of childhood, adolescence, adulthood and public life as a progression of one to the other, leading to a final blending of subject in the last c story, "The Dead". The path that leads to the understanding of this blending goes through diverse by-ways, all of them oriented by the study of transtextual relations Joyce's style, the relationship between his life and work, and the inescapable internal allusions within his fiction and his letters.